(untitled) (Nigerian Journal of Physiological Sciences, 2019)
The African Catfish (Clarias gariepinus) are important source of protein for local consumers in developing countries in Africa and have also been reported to have enormous commercial potential. Several works have been done on plethora of general histological, biochemical and hormone changes which accompany puberty in African Catfish. Other studies have touched the effects of ecotoxins on the histological and reproductive parameters of the mature African Catfish. This study is an attempt to use immunohistochemical and basic histology to elucidate the baseline information on the general structural differences between the testes of immature and post-pubertal catfish with respect to some intermediate filaments arrangement within the testicular tissue. Ten (10) each of mature male catfish (4-5 months old) and immature male catfish (3 months old) were used in the study. The fish were subjected to cold shock and decapitated before the testes were harvested from both groups. These tissues were fixed in Bouin’s fluid for 24 hours and subsequently transferred into 70% Ethanol. Testicular tissues from both groups were processed for paraffin embedding for routine staining with H&E; another set of tissues were fixed in 10% Neutral Buffered Formalin for testicular immunostaining techniques against Vimentin, Desmin, Cytokeratin and Smooth Muscle Actin (SMA) expression using standard methods. There is an increase in seminiferous luminal area/diameter in the mature catfish testis with the presence of mature spermatozoa in the lumen when compared with immature catfish testis which has small size of lumen with absence of mature spermatozoa. Testicular interstitium thickness remain relatively unchanged. SMA was markedly expressed in the cytoplasm of interstitial Leydig cells in the immature catfish testis whereas it was weak in its expression in the mature catfish. However, SMA was not expressed in the connective tissue proper in the testicular interstitium. Cytokeratin expression was also marked in the testicular capsule of immature catfish but was weak to absent in the mature catfish, however, both mature and immature catfish had moderate cytokeratin expression in their seminiferous tubule basement membrane. Desmin was strongly expressed in cytoplasm of immature germinal cells in the immature catfish testis but was moderate in its expression in the mature catfish testis. Vimentin expression was marked in the cytoplasm of immature germinal cells in both immature and mature catfish testis but weak in its expression in the Sertoli cell cytoplasm of both groups. This study infers that ultra-structural and protein changes can be related to age changes alone apart from the contribution of seasonality and external interference by ecotoxins. The age-related changes seen in this study could set ``baseline information. The extent of contribution of season and other external factors will be better understood. Though the age-related difference might be peculiar to the species of current interest, the differences elucidated are a sound background for relational studies, especially on the effect of ecologic toxins on immature testis, as separate from the mature testis.